The effect of education on anxiety of pregnant mothers before amniocentesis - Shahnaz Mojahed; Razie Sadat Tabatabaei; Fariba Reihani; Ali Dehghani; Faride Khavari (Journal of Education and Health Promotion, 2021)
BACKGROUND: Pregnancy alone is associated with many anxieties and worries for many women. Prenatal diagnosis of fetal malformations is one of the most important anxious events for women. Increasing knowledge empowers the person to identify the important issues and by increasing understanding, creates a positive attitude in people. Therefore, the aim of this study was to investigate the effect of education on the level of anxiety of pregnant mothers before invasive screening for fetal abnormalities (amniocentesis). MATERIALS AND METHODS: This is a quasi-experimental study with two parallel designs in three stages: Pretest (before intervention), posttest (after intervention), and after amniocentesis. This study was performed on 80 pregnant women candidates for amniocentesis (40 pregnant women in the control group and 40 pregnant women in the intervention group) referred to the perinatology clinic in Yazd in 2020. Data collection tools were demographic and midwifery questionnaires and Spiel Berger anxiety questionnaires. In the experimental group, the intervention was performed as group training for 90 min immediately before amniocentesis. In the control group, only routine procedures (brief description by a perinatologist during amniocentesis) were performed. SPSS software version 16 was used to analyze the data. RESULTS: The mean age of the research units was 67/5 ± 5/33 years. The results of Mann–Whitney intergroup test showed that the mean scores of overt anxiety before the intervention between the control and intervention groups were not significant (P < 0.014) but were significant after training and after amniocenter (P < 0.001). Furthermore, the results of Mann–Whitney group test showed that the mean scores of overt anxiety in the intervention group before and after training were significant (P < 0.001). Furthermore, the results of the control group showed significant results (P < 0.001). The results of the independent t-test showed that the mean scores of latent anxiety before the intervention between the control and intervention groups were not significant (P < 0.194) but were significant after the training (P < 0.57) but The results were not significant after amniocentesis (P < 0.216). Furthermore, the results of paired t-test within the group showed that the mean scores of overt anxiety in the intervention group before and after training was significant (P < 0.001). Furthermore, the results of the control group showed significant results (P < 0.001). CONCLUSION: The findings of the present study indicate the positive effect of education on anxiety of pregnant women candidates for amniocentesis. The results also show the important role of education on the psychological dimension of high-risk pregnant women in relation to the consequences of pregnancy and childbirth. According to the research results, it seems that education affects the cognitive system and information processing by increasing people's awareness of the amniocentesis process and its consequences.